Changes and determination of dosing recommendations for medicinal products recently authorised in the European Union. (April 2015) - Ehmann, Falk; Papaluca, Marisa; Di Giuseppe, Francesca; Pani, Luca; Eskova, Andrea; Manolis, Efthymios; Herold, Ralf
Abstract : Introduction: The quantity and quality of data for determining the dose and treatment schedule of medicinal products is directly related to how safe and efficacious these medicines are and how successful they can be used to treat patients. Areas covered: This review provides an analysis of dose-related label modifications of recently approved drugs. It shows which areas could benefit from a better dose–exposure–response understanding, both during initial assessment and after marketing authorisation. This analysis highlights regulators' considerations in dosage evaluations and provides reflections for drug developers on how to ensure best possible dose selection in the interest of the patients. Expert opinion: Using modelling and simulation, pharmacogenomics, population pharmacokinetics, physiologically based pharmacokinetic models and drug–drug interaction studies in conjunction with well-designed clinical trials will improve the understanding of the pharmacology of medicines, of the physiology of the disease and of the dose–exposure–response relationship during drug development. More focus should be given to the investigation of dose and regimens for special populations before applying for marketing authorisation. Consequently, regulators could review dose–exposure–response data with more certainty and better define dose recommendations in the label.